Anthropogenic features of salt marsh flora with varying substrate salinity, human impact and abundance of halophytes - Karasińska, Wiesława; Nienartowicz, Andrzej; Kunz, Mieczysław; Piernik, Agnieszka; Filbrandt-Czaja, Anna; Kamiński, Dariusz; Rutkowski, Lucjan (Ecological Questions, 2025)
The paper presents an assessment of the degree of flora synanthropization of salt marshes along the Noteć Canal in the vicinity of the soda works in Mątwy and Janikowo, the salt mine in Góra, and at the salt works and spa in Inowrocław, vestern Kuyavia. Salt marshes were located mainly along pipelines that supply brine from the mine to industrial production, medical care and recreation and pipelines that carry saline industrial and municipal wastewater to places of its disposal and, after preliminary treatment, to the Vistula River. In previous studies, we recorded the occurrence of 117 vascular plant species, which we assigned to geographical–historical groups. In this work, we present the results of further analysis, which includes the comparison of the salt marsh flora in terms of synanthropization indices with the flora of 55 natural and artificial sites from different regions of Poland. The flora of the compared sites developed under varying substrate moisture, history of use and intensity of human impact. The range of variability of these factors was extensive, as these were both natural and degraded ecological systems, including those developed on artificial substrates. Both facultative and obligate, halophytes played an essential role in the floristic composition of many of these sites. Numerical classification of a set of 56 floras characterised based on the values of 13 indices showed that, in terms of the degree of synanthropization, the flora of investigated salt marshes is most similar to the floras of meadows occurring in other regions of Poland, both to those in the vicinity of industrial plants and those of artificial biotopes. Numerical ordination, however, showed that the indices of permanent synanthropization and total synanthropization, as well as the index of apophytism of spontaneophytes, contributed most to the variability. Differences in the values of 13 indices of synanthropization of selected floras from the five main subgroups distinguished in the numerical classification and ordination are presented by the graphical method.